2020
DOI: 10.1111/jcpt.13183
|View full text |Cite
|
Sign up to set email alerts
|

QTc prolongation during antiviral therapy in two COVID‐19 patients

Abstract: What is known and objective Acquired long QT syndrome secondary to drug‐induced QT prolongation and torsades de pointes has been reported for antiviral drugs. However, no studies have reported an association between corrected QT (QTc) prolongation and antiviral therapy in patients with novel coronavirus disease (COVID‐19). Case description We present two cases from our institution in which patients with COVID‐19 experienced QTc prolongation during treatment with antiviral therapy. Lopinavir/ritonavir, together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Two cases of increased QTc interval by administration of lopinavir/ritonavir combination reported by Zhu et al [42] provide further evidence on the relation of conduction abnormalities and antiviral drugs. In both cases, cessation of adverse effect causing drug leads to normalized QT intervals and eventual discharge from the hospital.…”
Section: Lopinavir/ritonavirmentioning
confidence: 65%
“…Two cases of increased QTc interval by administration of lopinavir/ritonavir combination reported by Zhu et al [42] provide further evidence on the relation of conduction abnormalities and antiviral drugs. In both cases, cessation of adverse effect causing drug leads to normalized QT intervals and eventual discharge from the hospital.…”
Section: Lopinavir/ritonavirmentioning
confidence: 65%
“…Interestingly, in this analysis, although critical QT prolongation was associated with higher risk of TdP, only treatment with LPN/RTV, simultaneous administration of amiodarone (known to prolong QT interval 52 ) or furosemide and hypokalemia could predict the occurrence of TdP in this cohort; instead, HCQ use was only modestly associated with TdP (0.3% of patients). Other cases of QT prolongation with LPN/RTV treatment have been described during the pandemic 53 , so that careful QTc duration evaluation and monitoring should be performed at baseline and during this drug therapy to identify patients at high risk of arrhythmias.…”
Section: Mechanisms Of Qt Prolongationmentioning
confidence: 99%
“…However, due to its enzymatic properties, it could increase the plasma concentration of the co-administered drug (lopinavir); hence, it could increase the risk of hepatotoxicity. 30 A case study conducted by Zhu, et al 31 no studies have reported an association between corrected QT (QTc found a side effect of QT prolongation during the administration of lopinavir/ritonavir in COVID-19 patients. Because of the side effects caused by therapy, the complications must be given attention as they can affect the clinical condition of the patients.…”
Section: Side Effects Of Lopinavir/ritonavirmentioning
confidence: 99%